2016
DOI: 10.1089/end.2015.0747
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Changes Inside the Kidney: What Happens During Holmium:Yttrium-Aluminium-Garnet Laser Usage?

Abstract: Laser use during flexible ureteroscopy may cause increased intrarenal temperatures. Rapid increases should be kept in mind when irrigation is closed. The irrigation seems to limit the temperature increase when used with any laser setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…More recent in-vitro studies confirm our results. Butticè et al 13 used the K-box ® polyurethane model (Coloplast, Humlebaek, Denmark) and demonstrated rapid rises in temperatures similar to our results. Their study showed a more pronounced rise with a larger laser fiber (272 versus 200 μm); however, this was not statistically significant.…”
Section: Looked Atsupporting
confidence: 88%
See 1 more Smart Citation
“…More recent in-vitro studies confirm our results. Butticè et al 13 used the K-box ® polyurethane model (Coloplast, Humlebaek, Denmark) and demonstrated rapid rises in temperatures similar to our results. Their study showed a more pronounced rise with a larger laser fiber (272 versus 200 μm); however, this was not statistically significant.…”
Section: Looked Atsupporting
confidence: 88%
“…A few recent series have reported on the temperature rise with laser activation. [11][12][13] The objective of this in-vitro study is to determine the time it takes after laser activation to heat fluid from body temperature (37°C) to 60°C at selected laser energy and frequency settings.…”
Section: Introductionmentioning
confidence: 99%
“…Intrapelvic temperature rises fast when using laser technology at high frequency and energy. This results in alterations of normal cellular functions and cell death . Currently, there is no scientific evidence to support that a UAS provides a cooling effect of the surrounding tissue by increasing irrigation outflow.…”
Section: Resultsmentioning
confidence: 99%
“…In 2004 Gyrus ACMI introduced the first totally digital flexible ureteroscopic system, the DUR-D Invisio platform [ 2 ]. This was a watershed moment as all the major companies began producing digital flexible ureteroscopes from that moment forward with an improved armamentarium available for the urologist [ 3 ]. In October 2015 Boston Scientific introduced the LithoVue™.…”
Section: Introductionmentioning
confidence: 99%